2016
DOI: 10.1007/s00216-016-0048-1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid analysis of bile acids in different biological matrices using LC-ESI-MS/MS for the investigation of bile acid transformation by mammalian gut bacteria

Abstract: Bile acids are important signaling molecules that regulate cholesterol, glucose, and energy homoeostasis and have thus been implicated in the development of metabolic disorders. Their bioavailability is strongly modulated by the gut microbiota, which contributes to generation of complex individual-specific bile acid profiles. Hence, it is important to have accurate methods at hand for precise measurement of these important metabolites. Here, a rapid and sensitive liquid chromatography-tandem mass spectrometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
69
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 51 publications
4
69
2
1
Order By: Relevance
“…The Actinobacteria represented in the phylogeny, from the family Coriobacteriaceae, are of particular interest due to previous reports of 12␣-HSDH activity. Wegner et al demonstrated that mouse fecal isolate Enterorhabdus mucosicola DSM 19490 T expresses bile salt hydrolase, as well as 3␣-HSDH and 12␣-HSDH activities (36). Our phylogenetic analysis suggests that the NAD(P)-dependent oxidoreductase (accession no.…”
Section: Resultsmentioning
confidence: 71%
“…The Actinobacteria represented in the phylogeny, from the family Coriobacteriaceae, are of particular interest due to previous reports of 12␣-HSDH activity. Wegner et al demonstrated that mouse fecal isolate Enterorhabdus mucosicola DSM 19490 T expresses bile salt hydrolase, as well as 3␣-HSDH and 12␣-HSDH activities (36). Our phylogenetic analysis suggests that the NAD(P)-dependent oxidoreductase (accession no.…”
Section: Resultsmentioning
confidence: 71%
“…Some unusual BA species with hydroxylation sites on C-1, 2, 4, 6 and 19 have been detected in biological samples in early human life and in patients with liver diseases. However, these challenges have not yet been addressed by LC-MS techniques currently used in BA analysis [2024]. Unusual species have seldom been detected using LC-MS, except for a recently-characterized CYP3A-mediated hydroxylated metabolite of DCA, 1β, 3α, 12α-trihydroxy-5β-cholan-24-oic acid (DCA-1β-ol) [2527].…”
Section: Introductionmentioning
confidence: 99%
“…Eggerthella lenta (formerly Eubacterium lentum) is a Gram-positive, non-sporeforming, nonmotile, obligate anaerobic bacterium whose growth is stimulated by arginine (17,18). E. lenta is a particularly important participant in the gut sterolbiome, various strains of which have the potential to encode enzymes that metabolize cardiac glycosides (19,20) and 21-dehydroxylate corticosteroids (21), hydrolyze conjugated bile acids (22), and oxidize bile acid hydroxyl groups (23,24). E. lenta strains have previously been grouped according to their pattern of hydroxysteroid dehydrogenase (HSDH) activities, with some strains having no HSDH activity (group V) and others expressing 3␣-HSDH, 3␤-HSDH, 7␣-HSDH, and 12␣-HSDH (group III) (24).…”
mentioning
confidence: 99%